Exploring determinants and strategies for implementing self-management support text messaging interventions in safety net clinics. Issue 1 (15th November 2022) - Nelson, Lyndsay A.; Roddy, McKenzie K.; Bergner, Erin M.; Gonzalez, Jesus; Gentry, Chad; LeStourgeon, Lauren M.; Kripalani, Sunil; Hull, Pamela C.; Mayberry, Lindsay S.
Abstract: Background: Text message-delivered interventions for chronic disease self-management have potential to reduce health disparities, yet limited research has explored implementing these interventions into clinical care. We partnered with safety net clinics to evaluate a texting intervention for type 2 diabetes called REACH (Rapid Encouragement/Education And Communications for Health) in a randomized controlled trial. Following evaluation, we explored potential implementation determinants and recommended implementation strategies. Methods: We interviewed clinic staff (n = 14) and a subset of intervention participants (n = 36) to ask about REACH's implementation potential. Using the Consolidated Framework for Implementation Research (CFIR) as an organizing framework, we coded transcripts and used thematic analysis to derive implementation barriers and facilitators. We integrated the CFIR-ERIC (Expert Recommendations for Implementing Change) Matching Tool, interview feedback, and the literature to recommend implementation strategies. Results: Implementation facilitators included low complexity, strong evidence and quality, available clinic resources, the need for a program to support diabetes self-management, and strong fit between REACH and both the clinics' existing workflows and patients' needs and resources. The barriers included REACH only being available in English, a lack of interoperability with electronic health record systems, patients' concerns about diabetes stigma, limited funding, and high staff turnover. Categories of recommended implementation strategies included training and education, offering flexibility and adaptation, evaluating key processes, and securing funding. Conclusion: Text message-delivered interventions have strong potential for integration in low-resource settings as a supplement to care. Pursuing implementation can ensure patients benefit from these innovations and help close the research to practice gap.